Adopting Intercultural Communication Issue in Teaching English - Hussain Ahmed Liton (Lingua Cultura, 2016)
Cultural assimilation and intercultural awareness has been an important hub of modern language and communication studies, underlining a shift that reflects a greater significance of the inseparability of language and culture, and the need to prepare students for effective intercultural communication to thrive in a global work environment. A thriving global workplace requires effective communication skill across cultures in this era of globalization and mass migration. Under the tutelage of such backdrop, this article addresses the terrain of adopting intercultural awareness in EFL classroom teaching/learning and aims at linking culture with language in pursuit of excellence in borderless effective communication. The study, in other words, investigated the linguistic aspects that could be affected by certain cultural dimensions (e.g., beliefs, traditions, taboo words, habits, and norms, religion, social factors, etc.) in intercultural communication. This paper uses a questionnaire device to receive some university teachers’ self-reported feedback. This article maintains qualitative and quantitative research methodology. The analytical research result shows that in teaching English, it is necessary to incorporate and develop aspects of cross-cultural awareness as a part of course curriculum to immerse students in effective intercultural communicative competence (ICC).